Entrepreneurial Leadership Nabi Muhammad Saw dalam Peristiwa Hijrah - Andi Susanto (STID Al-Hadid, 2022)
This article departs from the problem of leadership, which cannot get da'wah organizations out in a crisis situation. This is especially the case for da'wah leaders or organizations with da'wah missions. This article describes the entrepreneurial leadership carried out by the Prophet Muhammad SAW in the early prophetic events until the migration to Medina. This article uses an entrepreneurial leadership theory approach, and uses a qualitative library research approach. The results of this study show that the Prophet Muhammad had the ability to (1) take risks in taking opportunities to achieve da'wah goals, (2) creativity in finding existing opportunities, (3) visionary in providing energy to human resources, (4) innovative in utilizing resources to implement ideas in da'wah efforts.